The influence of spiritual well-being on burnout in kindergarten teachers with self-efficacy as a mediating variable - Rambe, Rifatun Nihaya; Hasanuddin, Hasanuddin; Hardjo, Suryani (Science Midwifery, 2026)
Improving the quality of human resources is a national strategic agenda, with early childhood education playing a crucial role in shaping cognitive, social, emotional, and spiritual foundations. Kindergarten teachers face complex work demands that are prone to burnout. Spiritual well-being, the ability to feel meaning, inner peace, and spiritual connectedness, is believed to protect teachers from stress and enhance a positive outlook on work. Self-efficacy, or self-belief, plays a role in strengthening teachers' ability to face challenges, manage the classroom, and remain productive. This study aims to understand the relationship between spiritual well-being, self-efficacy, and burnout in kindergarten teachers as a basis for developing psychological interventions. This quantitative correlational study used an online questionnaire with 200 kindergarten teachers in North Labuhanbatu, analyzed using PLS-SEM to test reliability, validity, and model fit. Spiritual well-being was measured using the SWBS (Paloutzian & Ellison, 1983), burnout using the Maslach Burnout Inventory (MBI), and self-efficacy using Bandura (2006). The results showed that Spiritual Well-Being had no significant effect on burnout (β = 0.080; p = 0.581), self-efficacy was also not significant on burnout (β = −0.186; p = 0.180), but Spiritual Well-Being had a significant positive effect on self-efficacy (β = 0.768; p < 0.001). The indirect effects analysis showed that self-efficacy was not a mediator (β = −0.143; p = 0.184; 95% CI = −0.353 to 0.068). Thus, the effect of Spiritual Well-Being on kindergarten teacher burnout is more complex and requires other mediators, such as coping strategies or emotional regulation, to be effective.